Using of special knowledge of investigation in the case of the killing of a newborn child by the mother - Антощук, Андрій Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Special knowledge of the investigator and the court used both during pre-trial investigation, and by obtaining information and advice from competent persons, the involvement of specialists of different profiles for their participation in the investigation (investigation) actions, the examination. During pre-trial investigation, the special knowledge is used in various procedural forms. The investigator and an expert apply them during the investigation (investigation) actions, such as inspection, search, etc. In turn the expert during the examination. The expert’s conclusion, according to the criminal procedure code of Ukraine, is considered a procedural source of evidence (part 2 of article 84). The success of the investigation into the murder of a mother for her newborn child depends largely on the timely and complete removal and appointment, together with the seized evidence of all required examinations. Urgent and information the examination is a forensic examination of the corpse of a newborn baby. During the investigation of murder by mother of her newborn child there is a need to conduct other examinations, including forensic-biological, cytological and immunological. Such studies are primarily aimed at the analysis of fingerprints, DNA – the carrier of genetic information from entities of living matter (blood, saliva, hair, etc), found at the scene.Traditional questions are the following: created be any substance of biological origin; whether the blood belongs to man or animal; what is the mechanism of formation of a trace of blood; at what distance, with what force, at what angle the blood fell on the subject; what type, group, RH blood of the victim (or the suspect); what is the limitation of the formation of a trace of this substance; are homogeneous substances of biological origin that were discovered at the scene or confiscated from a suspect, and the like. Of key importance in the investigation of killings in this category, in particular for the diagnosis of the mental condition of the suspect, having special knowledge in the field of psychology and forensic psychiatry. Consequently, the use of special knowledge in the investigation of the murder of the mother of your newborn child is a prerequisite of a qualified implementation. This knowledge is used during the investigation (investigation) actions, by carrying out examinations. The most characteristic for this crime examinations are considered to be of forensic medical expertise of corpse of a newborn, dactyloscopic, trasological examinations, forensic biology, cytological, immunological examination, psychological and psychiatric examination.